2021
DOI: 10.1097/md.0000000000028209
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management with remimazolam for a pediatric patient with Duchenne muscular dystrophy

Abstract: Rationale: With Duchenne muscular dystrophy (DMD) being the most common and most severe type of muscular dystrophy, DMD patients are at risk for complications from general anesthesia due to impaired cardiac and respiratory functions as the pathological condition progresses. In recent years, advances in multidisciplinary treatment have improved the prognosis of DMD patients, and the number of patients requiring surgery has increased. Remimazolam is a benzodiazepine derivative similar to midazolam. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…To date, there are only three previous reports regarding the administration of remimazolam in pediatric-aged patients ( Table 1 ) [ 16 - 18 ]. These reports describe the use of remimazolam in combination with remifentanil or propofol for TIVA during surgical procedures with endotracheal intubation, rather than as a primary agent for procedural sedation with a native airway as in our case report.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are only three previous reports regarding the administration of remimazolam in pediatric-aged patients ( Table 1 ) [ 16 - 18 ]. These reports describe the use of remimazolam in combination with remifentanil or propofol for TIVA during surgical procedures with endotracheal intubation, rather than as a primary agent for procedural sedation with a native airway as in our case report.…”
Section: Discussionmentioning
confidence: 99%
“…Remimazolam, like midazolam, is a potent GABA A receptor agonist [23], which is the hallmark property of many neurotoxic anesthetics [4,[35][36][37][38][39]. Interestingly, there is a report suggesting that remimazolam may negatively affect cognition in the elderly [40 ]. On the basis of the pharmacodynamic properties of remimazolam, there is currently no evidence to suggest it may be any different than other GABA A -agonists with regard to anesthesiainduced neurotoxicity.…”
Section: Andandmentioning
confidence: 99%
“…The patient did not display any signs of acute MH crisis through the second postoperative day. Additional anecdotal clinical work has suggested the safety and efficacy of remimazolam in various myopathic conditions including myotonic dystrophy and Duchenne muscular dystrophy [18,19]. Similar to MHsusceptible patients, TIVA is generally chosen in these patients due to concerns regarding the administration of volatile anesthetic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these potential advantages, remimazolam does not hold FDA approval for use in children and, to date, there has been only one previous anecdotal report of its use in a pediatric-aged patient. Horikosi et al reported the use of remimazolam as part of TIVA for a 4-year-old, 16 kg boy with Duchenne muscular dystrophy during inguinal herniorrhaphy and umbilicoplasty [18]. After the intravenous administration of fentanyl (100 µg), continuous infusions of remifentanil (1 µg/kg/min) and remimazolam (15 mg/h) were started.…”
Section: Discussionmentioning
confidence: 99%